ASPEK HUKUM PENGCOVERAN LAGU DITINJAU DARI UNDANG-UNDANG HAK CIPTA - Iwan Sandi Panagarso; Calvindo Bagas (Jurnal Justiciabelen, 2020)
Factors affecting the violation of copyright in songs or music in Indonesia are economic factors, socio-cultural factors, educational factors, weak law enforcement against violators. The forms of copyright infringement in Indonesia, namely Bootleg, namely piracy committed when the singer performs (Live Show). Counterfeit is a song hijacking done by copying directly, copying the cover and packaging exactly and Pirate is done by using various songs and various record albums that sell in the market.